2020
DOI: 10.1007/s00125-020-05133-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ertugliflozin on renal function over 104 weeks of treatment: a post hoc analysis of two randomised controlled trials

Abstract: Aims/hypothesis This study aimed to evaluate the effect of ertugliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, on eGFR and albuminuria (urine albumin/creatinine ratio [UACR]) vs glimepiride or placebo/glimepiride (non-ertugliflozin) over 104 weeks of treatment in participants with type 2 diabetes mellitus, using pooled data from two randomised controlled, active comparator studies from the eValuation of ERTugliflozin effIcacy and Safety (VERTIS) programme (Clinicaltrials.gov NCT01999218 [VERTIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 48 publications
4
30
0
3
Order By: Relevance
“…This check-mark effect suggests reduced hyperfiltration at the beginning of SGLT2i treatment that translates into the preservation of kidney structure over the long term. This peculiar hemodynamic sign heralding better kidney outcome has been a consistent finding in all the early SGLT2i trials [ 8 , 9 , 10 , 11 ], as well as in the most recent VERTIS trial in diabetic patients treated with ertuglifozin [ 44 ].…”
Section: The “Check-mark Sign” (√) In Patients Starting Sglt2i Thesupporting
confidence: 56%
See 1 more Smart Citation
“…This check-mark effect suggests reduced hyperfiltration at the beginning of SGLT2i treatment that translates into the preservation of kidney structure over the long term. This peculiar hemodynamic sign heralding better kidney outcome has been a consistent finding in all the early SGLT2i trials [ 8 , 9 , 10 , 11 ], as well as in the most recent VERTIS trial in diabetic patients treated with ertuglifozin [ 44 ].…”
Section: The “Check-mark Sign” (√) In Patients Starting Sglt2i Thesupporting
confidence: 56%
“…Table 1 summarizes the findings of RCTs with available results on GFR changes, comparing early (first few months) with subsequent months of treatment in experimental and placebo arms. As previously mentioned, all major trials with SGLT2i demonstrate a checkmark effect that is consistently associated with better renal outcome [ 8 , 9 , 10 , 11 , 44 ]. Figure 1 is a graphical description of the checkmark phenomenon, reporting the mean eGFR changes within the initial six months of trials and in the subsequent period of follow-up in patients administered with an experimental drug or placebo.…”
Section: The Check-mark Sign: Not Only Sglt2imentioning
confidence: 99%
“…A 24-week Japanese study of ipragliflozin in people with T2D reported larger changes in eGFR from baseline for ipragliflozin versus placebo in patients with moderate renal impairment (eGFR 30 to < 60 mL/min/1.73 m 2 ) compared with those with mild impairment (eGFR 60 to < 90 mL/min/1.73 m 2 ; − 2 mL/min/1.73 m 2 vs − 0.5 mL/min/1.73 m 2 ) [ 63 ]. Other studies have reported no significant changes in eGFR during longer term treatment with empagliflozin [ 64 66 ], canagliflozin [ 67 69 ], dapagliflozin [ 60 , 70 , 71 ], ipragliflozin [ 72 , 73 ], ertugliflozin [ 74 ], or tofogliflozin [ 75 ]. All SGLT2 inhibitor CVOTs report an initial rapid reduction in eGFR, followed by a slower decline, or stabilization, in the SGLT2 inhibitor group compared with placebo, explaining the greater decline in eGFR after 12 weeks that was reported in some studies.…”
Section: Renoprotective Effects Of Sglt2 Inhibitors According To Basementioning
confidence: 99%
“…Regression of albuminuria (return to ACR B 3 mg/ mmol) was increased by 30% in the CANVAS study (Table 2) [28,30]. Analysis of data from the DECLARE-TIMI 58 trial revealed a reduced risk in the renal composite end point (with dapagliflozin treatment versus placebo), and the DAPA-CKD trial was halted early in March 2020 [34,37].…”
Section: Renal Data From Sglt2i Cardiovascular Outcome Trialsmentioning
confidence: 99%
“…Analysis of data from the DECLARE-TIMI 58 trial revealed a reduced risk in the renal composite end point (with dapagliflozin treatment versus placebo), and the DAPA-CKD trial was halted early in March 2020 because of overwhelming efficacy [ 31 ]. The ertugliflozin VERTIS-CV trial demonstrated a 19% relative risk reduction with ertugliflozin for the composite renal end point, versus placebo, in people with T2DM and atherosclerotic cardiovascular disease (ASCVD) (Table 2 ) (and post hoc exploratory analysis using data from the VERTIS-SU and VERTIS-MET trials suggested that ertugliflozin provided improvements in eGFR and ACR compared with non-ertugliflozin treatment) [ 34 , 37 ].…”
Section: Sglt2i Treatments: Renal Outcomes Datamentioning
confidence: 99%